Patent Scope and Technology Choice - Erika Färnstrand Damsgaard (Research Institute of Industrial Economics (IFN), 2009)
This paper analyzes the effect of an increase in patent scope on R&D and innovation. It presents a model where patent scope affects an entrant firm's technology choice and thereby creates a trade-off between R&D investments and wasteful duplication of R&D. The model predicts that an increase in patent scope can increase the probability of innovation if the incumbents profit increase from innovation is large and the patented technology has a small advantage over the alternative technology. However, when the model is extended to Stackelberg competition or licensing, the benefit of a broad patent scope to a large extent disappears.
Keywords: K20; L51; 330; Innovation; Patents; Patent policy; Licensing; Patent; Innovation; Technologiewahl; Innovationsmanagement; Duopol; Theorie